Daily Saliva and Vaginal Mucins Co-vary in Protein-to-Carbohydrate Ratio - E. Baier, Robert; E. Meyer, Anne (Journal of Fertility Biomarkers, 2018)
The currently reported study employed the curiously named (but simple) quantitative, nondestructive technique of Multiple Attenuated Internal Reflection InfraRed (MAIR-IR) spectroscopy to assess daily variations of both saliva and vaginal secretions from a panel of consenting volunteers. The project goal was to determine whether the protein-to-carbohydrate (starch) ratio, determined by MAIR-IR analysis of salivary and vaginal secretions is an objective measure of the co-variation of mucinous secretions with daily menstrual cycle. Overall, the spectral data were found to provide valid signatures of vaginal mucus chemical changes that also correlated with cyclic periods of presumed fertility, such periods exhibiting repeat times of 14-16 days and 27-29 days in the thoroughly analyzed records. At mid-cycle, associated with ovulatory events, the protein-to-carbohydrate ratio of vaginal mucin maximizes. Higher carbohydrate ratios are associated with stiffer cervical mucus plug formation, which usually prevents infection, spontaneous abortion, and pre-term birth, but may also be responsible for infertility. Mucin relaxation compounds, such as the FDA-approved oral rinse, delmopinol, may induce fertility in such cases.
Keywords: glycoprotein; infrared analysis; periodicity; polysaccharide; saliva; secretions; spectroscopy ratios.